Blast injury lower face: An unusual and rare case - A Soni (Indian Journal of Plastic Surgery)
Isolated blast injuries of the face are rare and injuries due to blasting of low voltage batteries in or near the mouth are even rarer. We present here a case of an 18 year old boy who suffered from extensive injury and tissue loss involving the lower half of the face due to blasting of a low voltage battery used in a flash light due to apparent shortcircuiting when the boy put the two short wires connected to a low voltage battery in his mouth in order to deinsulate them. This resulted in a blast leading to severe injuries and tissue loss which included the lower nose, upper lip, all teeth, both cheeks, floor of mouth tongue, chin, the maxilla and mandible.